Assessment of Sarcopenia among Community-Dwelling At-Risk Frail Adults Aged 65 Years and Older Who Received Multidomain Lifestyle Interventions: A Secondary Analysis of a Randomized Clinical Trial - Lu, Y. (American Medical Association, 2021)
10.1001/jamanetworkopen.2019.13346